Kajian sosiologis: Implementasi tujuan pendidikan Islam dalam bermayarakat - Alis Kholisoh; Nur Khasanah (Jurnal Pendidikan Agama Islam, 2026)
The vision of education is an important element in the education system that serves as a guideline for the implementation of the learning process. The objectives of Islamic education are not only focused on religious aspects, but also pay attention to social and community aspects. This article aims to analyze the objectives of Islamic education from a sociological perspective, using library research methods and a qualitative approach. The results of the analysis reveal that the objectives of Islamic education have a significant impact on shaping the culture and way of life of society. Community-oriented Islamic education can help increase social awareness and active community participation in development. Thus, Islamic education plays a major role in creating a harmonious, just, and prosperous community.